Successful Treatment of Transplanted Kidney Patient with 100% Lung Damage Caused by COVID-19 Bilateral Pneumonia: a Clinical Case - R. R. Nuriakhmetov; V. S. Panteleev; A. R. Zagitov; M. A. Nartailakov; M. N. Kornilov; I. I. Biganyakov (Креативная хирургия и онкология, 2022)
Background. The new SARS-CoV-2 coronavirus infection is understudied; despite its worldwide prevalence, case reports of organ transplant recipients are rare.Aim. A dynamics evaluation and treatment outcome improvement in a transplanted cadaveric kidney patient with 100% parenchymal lung damage caused by SARS-CoV-2 coronavirus bilateral pneumonia.Materials and methods. We describe a successful treatment case of a transplant kidney patient having the new coronavirus infection (COVID-19) (of 03.12.2020). COVID-19 pneumonia was diagnosed on day 7 of the early post-transplant period. On day 14, the patient was admitted to an infectious ward and transferred to intensive care upon disease aggravation. Despite ongoing treatment, pulmonary parenchymal lesion reached 100% in CT scan on 24.12.2020. The patient was transferred to Surgery Unit No. 3 for further therapy on 11.01.2021 upon revealing a clinical improvement, positive laboratory dynamics and SARS-CoV-2-negative smear PCR tests. The patient was discharged for outpatient treatment on day 10.Results and discussion. No evidence of focal infiltrative pulmonary change was detected in control chest CT after 4 months. Within 5 months since discharge, there were observed a general well-being improvement, 98% oxygen saturation, absent oedema, satisfactory transplanted kidney function.Conclusion. Post-kidney-transplant patients are particularly susceptible to infection due to inherent chronic immunosuppression. The presented case of a kidney transplant patient having a favourable COVID-19 outcome demonstrates the efficacy of a timely treatment.